Waiting time for the final diagnosis of BI-RADS 4 and 5 - Carrillo-Sánchez, Leticia; García-Valdez, Ruth; Andrade-Amador, Verónica; Alvarez-Villaseñor, Andrea Socorro (Horizonte Sanitario, 2022)
Objective: To measure the waiting time in granting a final diagnosis to the rights holders with BI RADS 4 and 5 from 40 to 69 years old, in the General Hospital of the Zone + Family Medicine No.1 in La Paz, Baja California Sur, Mexico.Material and methods: Observational, descriptive study, with the review of 36 mammography control records from the radiology area, with BI RADS 4 or 5 results. Demographic variables and waiting times for the process were measured from mammography request until the final diagnosis. Descriptive statistics were performed. Study considered without risk according to the General Health Law. It was authorized by the ethics and research committees of the hospital unit.Results: A total of 36 screening files were analyzed in women between 40 and 69 years old, with a mean of 51.86 + 8.28 years. The average number of days elapsed from the request for the mammography to the final diagnosis was 125.05 + 66.23. In 13.9% of the cases, the diagnostic process was concluded in the normal scheduled time; for the remaining 86.1%, it took more than 30 days to complete the diagnostic protocol. The causes of the prolonged time were attributable to the delay in care at the second level (consultation of specialties and pathology area).Conclusions: It is necessary to generate strategies in all the steps of the process, to ensure that the waiting time regulated in the flowchart is complied with, both in the first and second level of care; to improve the prognosis of patients with breast cancer.Keywords: Time, Diagnosis, Breast cancer